Artificial Intelligence, Digital Civic Education, and Their Implications for Democratic Quality in Indonesia - Fitra Hadi Khaz; Amanda Meylani Dewi; Dhea Cantika; Bella Desvita; Hanna Zavira Nazla (Global Education Journal, 2025)
The rapid development of artificial intelligence (AI) has significantly transformed various aspects of public life, including political processes and civic engagement in Indonesia. Within the educational context, AI-driven political information circulating through digital platforms has become an informal learning environment that shapes citizens’ democratic understanding and political behavior. This study aims to analyze the use of artificial intelligence in the Indonesian political system and examine its implications for democratic literacy and civic learning. Employing a qualitative approach with a descriptive-analytical design, this research conducts a desk review and normative analysis of academic literature, policy documents, and relevant regulations related to AI, digital governance, and civic education. The findings indicate that AI technologies increasingly influence political learning through data-driven practices such as personalized political content, voter micro-targeting, automated public services, and digital election monitoring. While these developments offer opportunities for innovation and efficiency in civic learning, the unregulated and ethically ungrounded use of AI poses serious challenges to democratic education, including the spread of disinformation, manipulation of political awareness, data privacy risks, and unequal access to digital learning resources. These conditions may weaken critical thinking, political autonomy, and informed participation among learners and citizens. Therefore, the integration of AI literacy, ethical digital education, and democratic values within civic education is essential to ensure that AI contributes positively to the quality of democratic learning and sustainable democracy in Indonesia.